Variation of luminescence sensitivity of quartz grains from loess in eastern Tibetan Plateau and its provenance significance - Liu, Li; Yang, Shengli; Liu, Xiaojing; Li, Pushuang; Wang, Haiyan; Zhou, Jiantao (Frontiers in Earth Science, 2022)
The loess deposits widely distributed in the eastern Tibetan Plateau (ETP) are important archives for reconstructing the paleoenvironmental changes and dust transportation history of the Tibetan Plateau. A lack of sufficient investigations on the source of the ETP loess has limited our understanding of dust transportation and paleoenvironmental implications. Quartz luminescence sensitivity holds great potential for tracing eolian dust sources. Numerous quartz luminescence sensitivity investigations have provided new insights into the dust sources and transportation of the Chinese loess. However, studies on luminescence sensitivity and its significance for the ETP loess provenance are scarce. In this work, we selected quartz grains in loess from different sites of the ETP to investigate the variation of luminescence sensitivity by testing the 110°C thermoluminescence (TL) peak and optically stimulated luminescence (OSL) sensitivities of quartz grains and discussed the provenance implications for the ETP loess based on quartz luminescence sensitivities. Our results show the quartz luminescence sensitivities of loess at different locations were significantly different in the ETP. The luminescence sensitivity values of the Machang (MC), Xiaojin (XJ), and Wenchuan (WCH) sections were much higher than those of the Xinshi (XS) and Zhouqu (ZQ) sections. The sensitivity values of the 110°C TL peaks and OSL in the paleosol and loess layers show distinct differences. The quartz luminescence sensitivities of the ETP loess are mainly influenced by the dust sources. Our results show that the luminescence sensitivities of quartz grains have great potential for identifying the loess sources in the ETP.